Information Content of the Water Use Report by the Form No. 2TP-Vodhosp (Annual) - Panteleiev, V. P.; Kharlamov, O. I. (Statistics of Ukraine, 2022)
The solution to the problem of efficient use of water resources is largely based on reliable information about the state and dynamic movement of water resources during the calendar year both for individual water users and for Ukraine as a whole. To do this the legislator has applied a systematic approach to the reflection of water volumes: sets the volume of water inflow, namely, water intake / output, the amount of water actually used per year, transferred annual volumes of water and water losses, and drainage, i.e. return (wastewater) of various degrees of purification. Such data are summarized by collation the information from water users in river basins in the form of № 2TP-vodhosp (annual). The dominant requirements for streamlining information on water use by water users whose activities are related to water intake and / or use, discharge of return (waste) water and pollutants are identified: sources of water supply / water use; certain permits for special water use; limits of conditions for wastewater discharge; water use limits; compliance with the actual use of water for these needs. It was investigated the nature of information support of water use through the consideration of its accounting and reporting as a component of the state accounting of water use and the organizational principles of such accounting were determined. The classification of the forms of administrative reporting on the activities of water users is given. The essence of responsibilities of water users for the formation of data on the collection, use, transfer, loss of water and sewerage as a water user’s fulfillment of his obligations on state accounting of water use through elaboration of the content of the form of state accounting of water use by the form of № 2TP-vodhosp (annual). The requirements of normative legal acts on filling in the Report, the content of the Report form (22 items in total), the basis of information of three tables of the Report, the connection of the Report with the tax system, the comparative analysis of the content of Reports of different times research were traced; the conclusions from the conducted research are formulated and the directions of further research are outlined.